Cyclophosphamide for anticancer therapy-induced interstitial lung disease in the modern era: a retrospective cohort study - Katahara, Honami; Baba, Kaede; Nakajima, Hiromichi; Funasaka, Chikako; Kondoh, Chihiro; Naito, Yoichi; Udagawa, Hibiki; Shitara, Kohei; Sasaki, Tomoaki; Kawasaki, Toshikatsu; Mukohara, Toru (Frontiers in Oncology, 2025)
BackgroundDrug-induced interstitial lung disease (DIILD) is a serious complication of cancer treatment that is primarily treated with corticosteroids. However, effective standardized regimens for corticosteroid-refractory DIILD have not been established. Cyclophosphamide (CPA) is an immunosuppressant that is potentially effective against DIILD, but supporting evidence is limited, particularly for diseases induced by novel chemotherapeutic drugs. In this study, we examined the efficacy and safety of CPA in corticosteroid-refractory DIILD caused by various anticancer drugs.MethodsWe retrospectively reviewed the medical records of patients who underwent CPA therapy for corticosteroid-refractory DIILD at the National Cancer Center Hospital East between January 2013 and October 2023. Corticosteroid-refractory DIILD was defined as cases of DIILD classified as grade ≥3 according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0, in which no improvement was observed within 48 hours after initiating corticosteroid therapy. The primary endpoint was 30-day survival post-CPA. The secondary endpoints included radiological improvements and changes in oxygen supplementation.ResultsFifteen patients (median age 73 years; 80% male) were included in the analysis. Patients were classified into molecular-targeted drugs (MT; 20%, 3/15), MT + cytotoxic drugs (33%, 5/15), immune checkpoint inhibitors (ICI) ± cytotoxic drugs (27%, 4/15), and cytotoxic drugs alone (20%, 3/15) groups. The overall 30-day survival rate was 47% (7/15). Improvement of oxygen demand allowed 20% (3/15) of patients to discontinue oxygen supplementation. CPA demonstrated drug class-dependent efficacy: highest in the MT group (67% survival, 2/3), less benefit in the cytotoxic drugs alone group (0% survival, 0/3). Adverse events included grade 3 anemia (n=2), grade 4 neutropenia (n=1), and grade 2 cytomegalovirus infection (n=1), with no treatment-related deaths.ConclusionCPA exhibited potential efficacy for corticosteroid-refractory DIILD, particularly in patients with MT-induced DIILD, with manageable toxicity. The differential responses based on drug category suggest tailored approaches to DIILD management may be warranted. These findings may contribute to optimizing the management of severe DIILD during cancer treatment.